Inotuzumab ozogamicin versus standard of care in relapsed or refractory acute lymphoblastic leukemia: Final report and long‐term survival follow‐up from the randomized, phase 3 INO‐VATE study. Issue 14 (28th March 2019) - Kantarjian, Hagop M.; DeAngelo, Daniel J.; Stelljes, Matthias; Liedtke, Michaela; Stock, Wendy; Gökbuget, Nicola; O'Brien, Susan M.; Jabbour, Elias; Wang, Tao; Liang White, Jane; Sleight, Barbara; Vandendries, Erik; et al.
Abstract : Background: Inotuzumab ozogamicin (InO) is an antibody‐drug conjugate used for adults with relapsed/refractory B‐cell precursor (BCP) acute lymphoblastic leukemia (ALL). The INotuzumab Ozogamicin trial to inVestigAte Tolerability and Efficacy (INO‐VATE) previously reported improved outcomes with InO versus standard‐of‐care (SoC) chemotherapy. This article reports the final INO‐VATE results (≥2 years of follow‐up) and additional analyses of patient characteristics associated with improved outcomes. Methods: Between August 27, 2012, and January 4, 2015, this multicenter, parallel, open‐label, phase 3 trial randomized 326 adults with relapsed/refractory ALL to InO (n = 164) or SoC (n = 162); 307 received 1 or more doses of the study drug (164 in the InO arm and 143 in the SoC arm). Results: The complete remission (CR)/complete remission with incomplete hematologic recovery (CRi) rate was higher with InO versus SoC (73.8% vs 30.9%; 1‐sided P  < .0001), with consistent CR/CRi rates across patient subgroups. The median overall survival (OS) was 7.7 months with InO and 6.2 months with SoC, with 2‐year OS rates of 22.8% and 10.0%, respectively (overall hazard ratio, 0.75; 97.5% confidence interval [CI], 0.57‐0.99; 1‐sided P  = .0105). The predictors of OS with InO were the best minimal residual disease status, baseline platelet count, duration of first remission, achievement of CR/CRi, and follow‐up hematopoietic stem cell transplantation (HSCT; all 2‐sided P values < .05). More InO arm patients proceeded directly to HSCT after achieving CR/CRi before any follow‐up induction therapy (39.6% [95% CI, 32.1%‐47.6%] vs 10.5% [6.2%‐16.3%]; 1‐sided P  < .0001). The most frequent all‐grade and grade 3 or higher adverse events in both arms were hematologic. Veno‐occlusive disease (VOD)/sinusoidal obstruction syndrome (SOS) was more frequent with InO (23 of 164 [14.0%] vs 3 of 143 [2.1%]). Conclusions: In patients with relapsed/refractory BCP ALL in INO‐VATE, InO was associated with a greater likelihood of CR/CRi across key patient subgroups, and it served as a bridge to HSCT. Potential VOD/SOS risk factors must be considered when InO treatment decisions are being made. Abstract : All key subgroups of patients with relapsed or refractory CD22‐positive B‐cell precursor acute lymphoblastic leukemia have the potential to benefit from inotuzumab ozogamicin in comparison with the standard of care (intensive chemotherapy). In the future, the combination of inotuzumab ozogamicin with other therapies may provide improved outcomes.